(3eYGde GdOjf aj abg Bd jGSjfs - (3GdbWGf, eMeO Hf TLGY GdCfUGQj, cGf MjG (B832(3g` (B1429(3es
(3ChdgG (B:s
(3ChdgG(B: (3GdMeO ddg GdPj Ndbfj ef hdOBOe GdPj cQe (B... (3aEf Chdi eG JhLgJ Edjg Gdgee hJhGVYJ dg JjLGf Gdbee HbGA fhY GdEfSGf hGdaGQb Hjf GdYOd hGdYOhGfs
(3BNQgG (B:s
(3BNQgG(B: (3GdebUO GdNGeS aj GdGSJjaGA hajg eHGMK, GdChd jLH (B.. (3GdYeO hGdYOhGf eY GdTQGFW caGOI GdLeY hGdbUGU hdG jLH GdOjI EdG UdkMGs
(3GdJhKjbGJ GdeQLYjI (B:s
(3eYLe GdeDdajf, L (B3: 341s
(3GdPQjYI, L (B21: 131s
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
(3ehGUaGJ GdhYGA (B:s
Keywords: (3abg GdePGgH GdCNQis